If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 = -25 Reorder the terms: 12 + 6x = -25 Solving 12 + 6x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = -25 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = -25 + -12 6x = -25 + -12 Combine like terms: -25 + -12 = -37 6x = -37 Divide each side by '6'. x = -6.166666667 Simplifying x = -6.166666667
| http://www.edmyt.com/cat/images/ques/clip_image010.png | | 2b-5b+4a=9 | | 2b-5+4b= | | X^2+y^2+9y=-1.25 | | -1.5*B+B=9 | | 3[6+8(8-4)]= | | x+.09x=100000 | | 0.666=2.5y | | 5x^2+50x=105 | | a+a*a=0.75 | | 2x-(5x-10)= | | 0.666=2.5 | | 28t+3p=55 | | 6x+3=-3+3x+21 | | d(x/y) | | 4(2n+5)=8(9n+3)+1 | | y=-x^2+2x+15 | | .6666667x-12=(-2) | | 1.2x=90 | | s-12.50=34.25 | | x-(2-x)-(-x)=2(-x+5)+2x+18 | | 139+123456578= | | 2a-3b=-4 | | =8y+15y | | 8-3(m+4)=7 | | 10b+5=15 | | -4(2x-6)=12x-16 | | an=13(2)n-1 | | (2+x)(2+x)=1+x^2 | | an=2n-1-2 | | 21.00+0.16x=85 | | a=4+-7n |